Determinants Of Motor Vehicle Taxpayer Compliance In Sidoarjo District - Rahmawati, Maretta Ayu; Ratnawati, Rr. Dyah (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: To determine and analyze whether tax literacy, sanctions, benefits, and payment digitalization affect motor vehicle taxpayer compliance in Sidoarjo, which aims to support the increase in local tax revenue and academic discourse in tax accounting. determeheof pyments a Methodology. Methodology: A quantitative approach with 100 respondents selected via the Slovin formula from Sidoarjo’s taxpayer population. Accidental sampling was used to distribute questionnaires. SmartPLS 4.0 was applied for outer and inner model testing, and hypothesis analysis. Result: The tax sanction variable has a positive effect on taxpayer compliance with a p values of 0.015 and a t statistics of 2.444. The tax payment digitization variable has a positive effect on taxpayer compliance with a p values of 0.017 and a t statistics of 2.390. Meanwhile, the variable of tax literacy and tax benefits have no effect on taxpayer compliance because the p values> 0.05 and t statisticss < 1.96. Findings: Compliance is more strongly influenced by enforcement mechanisms and practical conveniences than by knowledge or perceived return. Respondents were more motivated by avoiding penalties and the ease of paying digitally than understanding tax concepts or benefits. This reflects gaps in public perception and trust in government efficiency and fairness. Originality: This study uniquely investigates compliance in Sidoarjo, where public trust is strained by local governance issues. Novelty: It highlights how digitalization and sanction enforcement operate as primary motivators in a region facing infrastructural and administrative challenges. Conclusion: Sanctions and digital payment systems significantly boost tax compliance, while literacy and benefits do not. Broader sampling and additional variable are recommended for future research to deepen insights. Type of Paper: Empirical research paper.